The Investigation of The Factors Affecting Students’ Speaking Difficulties in EFL Classroom at SMP Negeri 12 Denpasar - Ni Nyoman Tria Radharani Mahima Della; Ni Putu Ratni; Made Iwan Indrawan Jendra (Educational Journal, 2026)
This study highlights the importance of understanding students’ speaking difficulties in order to improve the quality of English language teaching, particularly in junior high school. Many students still face problems in expressing their ideas orally, even when they understand the material. These difficulties indicate that speaking is not only influenced by linguistic ability but also by emotional and cognitive factors. Therefore, this study aims to analyze the types of students’ speaking difficulties and the factors affecting those difficulties in class VII-B SMP Negeri 12 Denpasar. This study employed a descriptive qualitative research design. The data were collected through classroom observation, interviews with one teacher and three students, and documentation. The analysis was conducted using qualitative data analysis techniques, including data reduction, data display, and conclusion drawing. The study was supported by two main theories, namely Humanistic Learning Theory and Cognitive Theory, to explain both emotional and mental aspects of speaking difficulties. Data validity was ensured through triangulation of sources and techniques. The findings revealed that students experienced several speaking difficulties, including fear of making mistakes, difficulty in speaking in front of the class, hesitation when speaking, limited vocabulary, and difficulties in grammar and pronunciation. These difficulties were influenced by psychological factors, linguistic factors, cognitive factors, and external factors. These factors were interconnected and contributed to students’ low speaking performance. The study concludes that students’ speaking difficulties are complex and influenced by multiple factors that must be addressed simultaneously.